Functionalized indoles: hetero- and macrocyclization, coordination chemistry, and biological properties / Hamid Khaledi - Khaledi, Hamid (2012)
Three indolyl-imine ligands have been synthesized through the condensation of S-benzyldithiocarbazate with indole-2-carbaldehyde, indole-3-carbaldehyde and indole-7-carbaldehyde. Treatment of these Schiff bases with acetate salts of Ni(II), Zn(II) and Cd(II) in ethanol yielded a series of complexes of 2:1 type (ligand/metal ratio) in which the ligands coordinated to the metal ions as monoanionic N,S-bidentate chelates. While the 2-imineindole and 3-imineindole formed the expected five-membered chelate rings, the X-ray crystal structure of [Cd(HL3)(py)2], (HL3 = the mono-deprotonated 7-imineindole), revealed an unusual mode of coordination, namely formation of four-membered rings with the metal atom. Reaction of the 7-imineindole with the metal ions in the presence of potassium hydroxide produced complexes of the type [M(L3)(H2O)] in which the Schiff base acts as a dianionic N,N,S-tridentate ligand. A new series of gallic hydrazones containing an indole moiety was synthesized through the reaction of gallic hydrazide and different indole carboxaldehydes. Their antioxidant activities were determined on DPPH radical scavenging and inhibition of lipid peroxidation. The in-vitro cytotoxic activities of the compounds were evaluated against HCT-116 (human colon cancer cell line) and MCF-7 (estrogendependent human breast cancer cell line) by the MTT method. An attempt was made to correlate the biological results with their structural characteristics. A limited positive structure activity relationship was found between cytotoxic and antioxidant activities. The reaction of the potential multidentate ligand, 2-(diformylmethylene)-3,3-dimethylindole (diformyl) with M(OAc)2 (M = CoII, NiII, CuII, ZnII, CdII, and PdII) afforded a series of metal complexes with different nuclearity in which the mono-deprotonated diformyl behaves as an N,O-bidentate chelate or N,O,O-tridentate chelating-bridging agent. The bonding modes of the ligand and thus the structures could be modified to some extent by further treatment of the complexes with an ancillary ligand (methanol, pyridine, or 4,4-bipyridine). In the case of the palladium(II) complex, the pyridine and 4,4-bipyridine adducts yielded C,N-chelation of the metal ion through the aldehyde carbon and indolic nitrogen of the doubly deprotonated diformyl. The resulting acyl–palladium complexes were further bridged into polymeric structures when the dianionic diformyl behaved as a C,N,O-chelating-bridging ligand.